Eksploitasi Anak Sebagai Pengamen Jalanan Di Kabupaten Madiun dalam Tinjauan Viktimologi dan Hukum Islam - Nabilla, Eva; Musyafa'ah, Nur Lailatul (Muqaranah, 2024)
The crime of child exploitation as street buskers causes victims. Child buskers are widely spread in various cities, including in Madiun Regency. This study aims to explain and analyze the victims of child exploitation as street buskers in Madiun Regency from the perspective of victimology and Islamic law. This study is an empirical legal research conducted in Madiun Regency. Data were obtained through and documentation. Interviews were conducted with victims and the civil service police unit. Meanwhile, documentation comes from a review of books, journals, anthologies, and sources available on the internet. The analysis used in this study is descriptive qualitative data analysis. This study concludes that the Madiun Regency civil service police unit collaborates with the social services and village officials in handling victims of child exploitation as street buskers. The main factor in the existence of victims of child exploitation in Madiun Regency is the power held by parents. Based on the theory of victimology, this is in accordance with the concept of power relations that victims do not have the power to refuse. In Islamic Law, child exploitation is part of the deprivation of rights and is included in the criminal penalty so that the perpetrator can be punished with ta'zir. Child exploitation violates maqāṣid al-sharī'ah , which is violating the principles of hifz al-din, hifz al-'aql, hifz al-mal, hifz al-nasl and hifz al-nafs.